Pack cementation of high chromium steel for high temperature application in steam condition - Farah Alia, Fauzi (2018)
The oxidation of high Chromium (Cr) steels in steam environment may cause retardation or evaporation of protective chromia (Cr2O3) layer, which reduces its corrosion resistance as boiler materials. This condition may cause reduction of boiler life time or failure during operation. Therefore, the effort to maintain the formation of Cr2O3 layer in this steam environment is crucial so that it can be used for longer operating time and at a higher operating temperature. In this research, pack cementation of Cr, also known as chromizing process, was introduced to diffuse Cr into the surface of T91 steel sample. The diffused Cr was expected to act as reservoir for the formation of Cr2O3 protective layer when the steel was exposed to high temperature steam oxidation. The steel sample was embedded inside an alumina crucible that contained pack mixtures of Cr powder as a masteralloy, NH4Cl powder as an activator, and Al2O3 powder as an inert filler. The alumina crucible then was heated inside tube furnace to the expected temperature for the pack cementation process. The environment inside the tube furnace was kept inert by flowing pure argon gas at 150 mL/min. The parameters being observed in this research were temperature of pack cementation (600o-1050oC) and composition of pack mixture (20wt.% Cr - 60wt.% Cr). The time for pack cementation process was kept constant at two hours. In the effect of pack cementation temperature, the composition of pack mixture was constant at 48wt.% Cr – 4wt.% NH4Cl – 48wt.% Al2O3. Field emission scanning electron/Energy dispersive Xray (FESEM/EDX) analysis showed that Cr started to diffuse into the steel from 800oC. Cr-carbide and Cr-nitride also formed on the surface of the steel, in which its existence was confirmed by Xray diffraction (XRD) result. The formation of Cr-carbide was due to outward diffusion of carbon from the steel, and the Cr-nitride may also be formed from the outward diffusion of N and also from the decomposition of NH4Cl. Overall, the pack cementation heated at 1050oC has showed the most homogeneous and continuous diffusion layer as compared to heating at 600oC and 800oC, with Cr-depth about 40 μm. From the different composition experiment, three compositions of pack mixture with different Cr concentration and higher activator content (20wt. % NH4Cl) were observed at 1050oC. From FESEM/EDX analysis, it was found that higher concentration of Cr and NH4Cl produce higher Cr-depth. The 60wt.% Cr produced Cr-depth around 64 μm and also more homogeneous as compared to the other composition. Cr-carbides and Cr-nitride were also detected in all samples. Furthermore, high temperature oxidation was conducted to the pack cemented steels at 1050oC. The oxidation was performed at 700ºC for 90 hours under the steam condition. It was found that the Cr2O3 still existed on the steel, and the Cr depth did not significantly change after the oxidation process. These results showed that Cr from the pack cementation process was able to become reservoir for the formation of Cr2O3 in high temperature steam oxidation, and its existence could be used for a longer oxidation time.